Manajemen Pendidikan di Smk Ma’arif 4 Kebumen - Bahrun ALi Murtopo.; Nunung Nurngaeni; Syifa Maulana; Durotul Ngaesi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2019)
This collaborative research by student lecturers was conducted to study education management in vocational secondary education institutions. The research location is at SMK Ma'arif 4 Kebumen. This research is qualitative with data collection techniques of interviews, observation and documentation. This research was conducted in July-August 2019. The research informants were the Head of SMK Maarif 4 Kebumen and a number of teachers and staff related to research. The results of this study are as follows: (1) curriculum and learning management, student management and counseling guidance, educator and educational staff management, and industrial relations management are all quite good, need improvement in development, innovation, and creation. Recommendations, education management in research locations still needs to be improved again to answer the needs of the times